2020
DOI: 10.17533/udea.acbi.v41n111a04
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal protein determination for submerged cultures of the medicinal mushroom <i>Ganoderma lucidum</i> (Ganodermataceae) with activity over the phytopathogen fungus Mycosphaerella fijiensis (Mycosphaerellaceae)

Abstract: Banana is one of the most important edible crops in the world, however, it’s attacked by different pathogens, one of the most prominent of these is the fungus Mycosphaerella fijiensis, causal agent of Black Sigatoka. The environmental and economic issues related to the pesticides used for its control have encouraged the search for cleaner alternative biomolecules. Previous studies were made by the Biotechnology group from the Universidad de Antioquia searching for a biological alternative for the control of M.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 65 publications
1
13
0
Order By: Relevance
“…One of these effects is antimicrobial activity against viruses, bacteria, fungi, and yeasts. The possible sources of antifungal activity for G. lucidum have been attributed to proteins (27), lipopolysaccharides (11), organic acids (15), and glycoproteins (34). The results related to antifungal properties of different parts of G. lucidum are inconsistent, and this difference can be attributed to the method of extraction and the type of harmful fungal strains.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of these effects is antimicrobial activity against viruses, bacteria, fungi, and yeasts. The possible sources of antifungal activity for G. lucidum have been attributed to proteins (27), lipopolysaccharides (11), organic acids (15), and glycoproteins (34). The results related to antifungal properties of different parts of G. lucidum are inconsistent, and this difference can be attributed to the method of extraction and the type of harmful fungal strains.…”
Section: Discussionmentioning
confidence: 99%
“…Also, several studies have shown the antifungal activity of G. lucidum against some harmful fungal species, including Aspergillusspp., Fusariumspp., Penicilliumspp. (15,(26)(27)(28)(29), and Candida albicans (30). Due to its significant properties, G. lucidum can be considered as a potential option for the production of new natural and healthy antifungal agents.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported the presence of enzymes with protease, chitinase, and glucanase activities in the crude protein extract of G. lucidum. These enzymes were linked to cell wall degradation and growth inhibition of Pseudocercospora fijiensis, a phytopathogen fungus that causes Black Sigatoka disease in Musaceae crops [4,5]. The use of these biomolecules as biological control agents in plants could help reduce or replace the pesticide amount applied in agriculture uses, contributing to the reduction of the environmental impact provoked by chemical agents conventionally used in the countryside.…”
Section: Introductionmentioning
confidence: 99%
“…This study aims to evaluate the effect of oxygen supply in a stirred tank bioreactor, through the variation of KLa initial value, on Ganoderma lucidum growth, exopolysaccharides production, and crude protein extract obtention [5]. The behavior of the fungus culture is shown through the kinetics of growth and the uptake of nutrients in a stirred tank bioreactor, operating in discontinuous mode and using a low-cost complex culture medium.…”
Section: Introductionmentioning
confidence: 99%